1994
DOI: 10.1111/j.1476-5381.1994.tb14886.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization and anatomical localization of prejunctional β‐adrenoceptors in the rat kidney

Abstract: 1 The subtype and anatomical localization of P-adrenoceptors mediating facilitation of stimulusinduced overflow of noradrenaline ('prejunctional P-adrenoceptors') are not conclusively known to date.The present study was undertaken to characterize these receptors by use of pharmacological methods as well as to define their localization (prejunctional or postjunctional) with radio-ligand binding and autoradiography techniques combined with surgical denervation of the sympathetic innervation to the rat kidney.2 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…On the other hand, it still remains controversial whether all β-adrenoceptor blockers have a prophylactic efficacy in migraine or it is limited to individual members of this drug class with specific characteristics. β-blockade results in (a) inhibition of noradrenaline release by blocking prejunctiononal β-adrenoceptors (Lakhlani et al 1994) and (b) a delayed reduction in tyrosine hydroxylase activity, the rate-limiting step in noradrenaline synthesis, in the superior cervical ganglia (Hieble 2000). It is also suggested that lipophilicity (penetration into the central nervous system), membrane-stabilizing effects and intrinsic sympathomimetic activity are relevant for antimigraine efficacy.…”
Section: β-Adrenoceptorsmentioning
confidence: 99%
“…On the other hand, it still remains controversial whether all β-adrenoceptor blockers have a prophylactic efficacy in migraine or it is limited to individual members of this drug class with specific characteristics. β-blockade results in (a) inhibition of noradrenaline release by blocking prejunctiononal β-adrenoceptors (Lakhlani et al 1994) and (b) a delayed reduction in tyrosine hydroxylase activity, the rate-limiting step in noradrenaline synthesis, in the superior cervical ganglia (Hieble 2000). It is also suggested that lipophilicity (penetration into the central nervous system), membrane-stabilizing effects and intrinsic sympathomimetic activity are relevant for antimigraine efficacy.…”
Section: β-Adrenoceptorsmentioning
confidence: 99%
“…, 1977; Vanter et al. , 1985) and there is convincing evidence that both β 1 ‐ and β 2 ‐adrenoceptors are present in the renal vasculature (Lakhlani et al. , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…, 2001). Studies of the anatomical localization of β‐adrenoceptor subtypes mediating facilitation of stimulus‐induced overflow of noradrenaline have suggested the presence of a homogeneous population of prejunctional β 2 ‐adrenoceptors (Lakhlani et al. , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ten animals were anesthetized with an IP injection of pentobarbital sodium (60 mg/kg) and laparotomized. The right renal artery was exposed and denervated by stripping the artery surgically and swabbing it with a 10% phenol solution dissolved in ethanol according to the procedure detailed elsewhere (Lakhlani et al 1994). The remaining rats were sham-operated.…”
Section: Animals and Tissue Treatmentmentioning
confidence: 99%
“…NE was assayed by high-pressure liquid chromatography (HPLC) with electrochemical detection (Lakhlani et al 1994). …”
Section: Ne Assaymentioning
confidence: 99%